MONITORING THE BEHAVIOUR OF KERA N ALLOY TO CORROSION IN AFNOR ARTIFICIAL SALIVA - Daniela-Mariana Calamaz; Naoun Nour Leila; Raluca-Elena Baciu; Maria Baciu; Irina Gradinaru (Romanian Society of Oral Rehabilitation, 2016)
Corrosion consists in the degradation of a material under the chemical or electrochemical action of the environment in which it is placed. The investigations carried out aimed at showing the behaviour of KERA N (Eisenbacher Dental - Waren ED GmbH, Germany) alloy to corrosion in AFNOR artificial saliva. In this study we used the linear polarization method at different scanning speeds and the cyclical polarization method. The corrosion potentials for Kera N alloy under study vary depending on the scanning speed of the potential between -927.5mV and -516 mV. From the cyclical polarization tests we noticed that the Ni-based alloy, Kera N (Eisenbacher Dental - Waren ED GmbH, Germany) shows a generalized corrosion type without the tendency to form pitting type corrosion.